2001
DOI: 10.1007/s004280000372
|View full text |Cite
|
Sign up to set email alerts
|

Association between nonbacterial thrombotic endocarditis and hypoxigenic pulmonary diseases

Abstract: Observation of patients with nonbacterial thrombotic endocarditis (NBTE) in the setting of hypoxia from various lung diseases raised the question of a possible pathogenetic relationship between hypoxia and the development of NBTE. We reviewed 50 autopsied patients with NBTE and compared them with 50 age/race/gender-matched control patients without NBTE. We noted the lung weight and graded the histopathological severity of lung involvement by disease, clinical respiratory compromise, and the extent of any cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Among these, association between NBTE and hypoxigenic pulmonary diseases has been suggested. 11 Clinical and experimental data suggest a causal relationship between hypoxia and NBTE. Experimental data from Nakanishi et al 12 demonstrated a greatly increased incidence on NBTE in rats subjected to a hypoxic environment.…”
Section: Discussionmentioning
confidence: 97%
“…Among these, association between NBTE and hypoxigenic pulmonary diseases has been suggested. 11 Clinical and experimental data suggest a causal relationship between hypoxia and NBTE. Experimental data from Nakanishi et al 12 demonstrated a greatly increased incidence on NBTE in rats subjected to a hypoxic environment.…”
Section: Discussionmentioning
confidence: 97%